André : André Leon Talley--a fabulously fashionable fairy tale - Weatherford, Carole Boston, 1956-; Sanders, Rob, 1958- (Henry Holt and Company, 2025)
This picture-book biography presents the life of André Leon Talley, tracing his early years in North Carolina through his rise in the international fashion industry. It describes formative influences, including his interest in magazines and fashion, and outlines challenges he faced growing up in the segregated South. The book highlights his career achievements and legacy, accompanied by illustrations that depict significant moments in his personal and professional development.